The effectiveness of the nationwide BokSmart rugby injury prevention program on catastrophic injury rates - Brown, J. C.; Verhagen, E.; Knol, D.; Van Mechelen, W.; Lambert, M. I. (Scandinavian Journal of Medicine & Science in Sports, 2016)
Rugby Union ("rugby") participants have a higher than average risk of injury compared with participants of other popular team sports. BokSmart, a nationwide injury prevention program was launched in South Africa in mid-2009, with the goal of reducing catastrophic head/neck (serious) injuries in players. The program provides injury prevention information to coaches and referees. This study investigated if BokSmart has been associated with a reduction in these injuries. The BokSmart program collected data on all South African rugby-related serious injuries since 2008. Using a Poisson regression, injury numbers were compared pre-BokSmart (2008-2009) to the years post-implementation (2010-2013). Player numbers were assumed to be constant throughout this evaluation: junior = 529?483; senior = 121?663. In junior players, the "post-BokSmart" period had 2.5 less annual serious injuries than "pre-BokSmart" (incidence rate ratio: 0.6, 95% confidence interval: 0.5-0.7, P < 0.000). In contrast, there was no significant difference in these periods in seniors. The absence of effect in seniors may be a result of fewer players or of differences in effectiveness of BokSmart in this group - future studies should investigate these questions.